Street-signs: The City as Context and as Code in the Novels of Claire Etcherelli - Sara Poole (Studies in 20th & 21st Century Literature, 1994)
The piece aims to consider the novels of Claire Etcherelli as examples of le roman parisien, and to examine the different roles the city is made to play in them. It looks briefly at Etcherelli's debt to the literature of the nineteenth century; at the significance of using real place names in such realist fiction; at Paris as political fulcrum; at why most of Etcherelli's characters live on the fringes of the city. The second half concentrates on Elise ou la vraie vie and attempts to illustrate how in this novel Paris becomes an extended and elaborate metaphor for that 'real' or 'true' life. The eponymous heroine is unable to penetrate the capital without simultaneously exploring her own coming to consciousness and sensual awareness, and she can achieve neither of these goals without the character given the role of initiator, her Algerian lover Arezki. The loss of the one therefore automatically incurs the loss of the other, and Paris becomes literally out of bounds to her.
Keywords: Claire Etcherelli; le roman parisien; city; city life; place; space; realist fiction; Paris; Elise ou la vraie vie